Improvement of inattentive and hyperactive symptoms after real-life rhinitis treatment in school-aged children. (June 2022) - Thamrongsak, Chatsuda; Chirdkiatgumchai, Vilawan; Jotikasthira, Wanlapa; Kiewngam, Potjanee; Kanchongkittiphon, Watcharoot; Manuyakorn, Wiparat
Abstract: Objectives: Rhinitis treatment may improve attention-deficit/hyperactivity symptoms in children. The current study evaluated changes in inattentive and hyperactive symptoms after treatment in children with chronic rhinitis. Methods: Children aged 5–18 years with chronic rhinitis were enrolled in a 3-month prospective study. The nasal provocation test for house dust mites (HDM) and evaluation of allergen sensitization, including the skin prick test and the Phadiatop test, were performed. The severity of rhinitis was assessed according to the ARIA guideline. The total nasal symptom score and the Vanderbilt ADHD Diagnostic Rating Scale (VADRS) score for assessing inattentive and hyperactive symptoms were recorded at baseline and at 1 and 3 months after rhinitis treatment. Children with rhinitis were classified into the following two groups: HDM-induced allergic rhinitis (AR group) and non-allergic rhinitis to HDM (NAR group) based on the NPT. Results: Overall, 83 children completed the 3-month prospective study, and they had a mean age of 9.12 ± 2.89 years and 44.6% were boys. After rhinitis treatment, VADRS scores assessed by the parents and teachers were significantly decreased compared with those at baseline (p = 0.005). In subgroup analysis, 61 (73.49%) children had AR, and 22 (26.5%) children had NAR. No significant difference in the baseline VADRS score was found between the AR and NAR groups. After treatment, VADRS scores assessed by the parents and teachers were significantly decreased only in the AR group (p < 0.001). Forty-five (54.2%) children had moderate persistent rhinitis, 29 (34.9%) had mild persistent rhinitis, and 9 (10.8%) had mild intermittent symptoms. There were no differences in baseline VADRS scores assessed by the parents and teachers among children with mild intermittent, mild persistent, or moderate persistent symptoms. The total nasal symptom score and VADRS score were significantly decreased after treatment for all severities of rhinitis compared with those at baseline. A greater baseline VADRS score was associated with substantial improvement of inattentive and hyperactive symptoms after treatment. Conclusion: Early treatment for rhinitis may improve inattentive and hyperactive symptoms in school-aged children.